Participatory Action Research for Learning Chemistry: A Case of Public Schools in Nepal - Acharya, Kamal Prasad (Journal of Advanced College of Engineering and Management, 2019)
The  present  study  reconnoiters  the  application  of  participatory  action  research  (PAR)  in  improving  the  performance  of students  in chemistry  sections. A mixed method research is  employed  focusing PAR as qualitative and experimental as a quantitative with  equivalent  groups. Two  schools were  purposively  selected  (one  leader  and  one  leader)  in Chitwan  and Nawalparasi districts. All the students in the leader school are given intervention. Thirty students from the feeder school are in control group. Intervention was done by laboratory activities in chemistry teaching. PAR approach is used in the leader school during intervention. Pre-test and post-test were used to collect the data. Data are analyzed using inferential statistics: independent student t-test  and  analysis  of  covariance  (ANCOVA).  The result shows that  the  experimental  group outperformed to control group suggesting that PAR approach enhanced performance of lower and high achievers more than the lecture method of teaching.